Proteômica do fluido da Rete Testis de carneiros Morada Nova - Sousa, Solange Damasceno (2015)
The aim of the study was to identify and characterize the proteins of the rete testis fluid from Morada Nova rams. The testicles, obtained from six slaughtered Morada Nova rams, were immediately dissected. The head of the epididymis was separated to gain access to the efferent ducts. The fluid from the efferent ducts was obtained by testis massage. Thereafter, the fluid was centrifuged to remove cell debris and sperm. Proteins were precipitated with acetone at -20°C and quantified by the Bradford assay. Each sample (400 µg) was focused in strips of 13 cm (pH 4-7) and the second dimension was conducted on SDS-PAGE 15%. The gels were scanned with an ImageScanner II (GE Lifesciences, USA) and analyzed using the PDQuest® version 8.0.1 (Bio-Rad Laboratories, USA). Spots detected after PDQuest analysis of 2-D maps were cut from gels and submitted to trypsin digestion. Proteins were identified using tandem mass spectrometry. Protein information obtained by MASCOT was analyzed using the software tool for searching annotations of proteins (STRAP). Protein-protein interaction networks were obtained from STRING version 9.0 database. In the gels were detected 227 ± 32.1 spots (mean ± SD), where 51% of the proteins were found above 40 kDa, corresponding to 65% of the intensity of all spots detected. Based on gene ontology analysis, the most common biological processes associated with proteins from rete testis fluid were regulation (24.28%) and cellular process (23.27%). Binding (27.42%) and catalytic activity (19.30%) corresponded to the most frequent molecular functions for those proteins. The most intensely expressed proteins were: albumin, clusterin, serotransferrin, immunoglobulin gamma-1 chain and alpha-2-HS-glycoprotein. The rete testis fluid has a large quantity of proteins related to the spermatogenesis. This feature is important in view of the fact that these molecules contribute to the development of the germ cells, as a result of the transport and conversion of substances required to the production of male gametes.